Cooperative projects linked to companies in Higher Education - Domingo Verano-Tacoronte; Silvia Sosa-Cabrera (Universitat Politècnica de València, 2015)
Developing   cooperative   projects   linked to  companies  is  considered  an  effective way to bring more realism to teaching in Higher  Education.  Getting  direct  contact with    firms    and    conducting    activities relate to them provide a complementary approach to the work done in classrooms, and   make   a   profound   mark   on   the students participating in them. This paper aims  to  prove  that  cooperative  projects linked  to  companies  makes  a  significant contribution  to  learning  and  satisfaction of students. To test this, we have analyzed, in  the  context  of  application,  a  course  of the fourth year of a Business Management Degree,  the  student  satisfaction  with  the different  elements  of  the  methodology (i.e. tutoring, assessment, skills acquired...) and  the  correlation  between  the  marks of  the  projects  and  the  exam  ones.  The results show that the methodology makes a   significant   and   positive   contribution in  both  areas,  as  most  of  its  elements has  been  well  rated  by  the  students,  and also that the grade obtained by them in the  project  is  positively  and  significantly correlated  with  their  final  exam  ratings. Furthermore,  it  is  noteworthy  that  the results obtained show that both faculty involvement in tutoring and assessment activities  and  clarification  of  the  students expectations  by  using  scoring  rubrics  for assessment,  are  critical  elements  in  the success of the methodology.